2010
DOI: 10.1074/jbc.m110.103358
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of the A1 Domain in von Willebrand Factor Dissociates the A1A2A3 Tri-domain and Provokes Spontaneous Binding to Glycoprotein Ibα and Platelet Activation under Shear Stress

Abstract: This study used recombinant A1A2A3 tri-domain proteins to demonstrate that A domain association in von Willebrand factor (VWF) regulates the binding to platelet glycoprotein Ib␣ (GPIb␣). We performed comparative studies between wild type (WT) A1 domain and the R1450E variant that dissociates the tri-domain complex by destabilizing the A1 domain. Using urea denaturation and differential scanning calorimetry, we demonstrated the destabilization of the A1 domain structure concomitantly results in a reduced intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 45 publications
4
76
0
Order By: Relevance
“…Previously, we described the functional similarities between a monomeric A1A2A3 protein and full-length vWF and suggested that the recombinant tri-domain fragment (amino acids 1238 -1874) of vWF contains regulatory structural elements that modulate activation of vWF in solution (4). On the other hand, another recombinant A1A2A3 protein (amino acids 1261-1874) from our laboratory apparently resulted in a GPIb␣ binding site that was less cryptic in the A1 domain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we described the functional similarities between a monomeric A1A2A3 protein and full-length vWF and suggested that the recombinant tri-domain fragment (amino acids 1238 -1874) of vWF contains regulatory structural elements that modulate activation of vWF in solution (4). On the other hand, another recombinant A1A2A3 protein (amino acids 1261-1874) from our laboratory apparently resulted in a GPIb␣ binding site that was less cryptic in the A1 domain.…”
Section: Discussionmentioning
confidence: 99%
“…However, the binding site for GPIb␣ in the A1 domain remained cryptic in our A1A2A3 protein, which excludes the DЈD3 domains (4). This outcome may indicate that the amino acid sequence 1238 -1247 from the C terminus of the D3 domain forms part of the mechanism that masks the binding site for GPIb␣.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Circulating platelets do not bind VWF unless putative conformational changes occur around its A1 domain that exposes the GPIb␣ binding site (VWF activation) as a result of high hemodynamic force (8). The present view of the force-dependent VWF activation includes two steps: 1) relief of an autoinhibitory mechanism involving interdomain associations within the A1A2A3 tri-domain (9,10) and between A1 and DЈD3 (11) and 2) upregulation of A1 binding affinity to GPIb␣ (6,(12)(13)(14). However, the biophysical and structural basis of how the VWF-GPIb␣ interaction is regulated when its hemostatic adhesive function is most needed remains unclear, in part, because of discrepant data.…”
mentioning
confidence: 99%